Alliance capitalism and the internationalisation of Finnish firms - Christopher Palmberg; Mika Pajarinen (The Research Institute of the Finnish Economy (ETLA), 2005)
The global surge in strategic alliances has led observers to coin the concept ”alliance capitalism” and suggest that they amount to a new logic of international business organisation and strategy. From the viewpoint of Finland, as a small and open economy, these developments can have far-reaching implications for the internationalisation strategies of firms, industrial renewal and competitiveness. Extant research points to a high degree of internationalisation of Finnish firms as measured by high-tech exports, international patenting and FDI. Nonetheless, little is known about the extent, nature and challenges of their alliance activities. This paper applies international business theories to give new insights into the role that alliances play in the overall internationalisation of major Finnish firms, the main motives and challenges that firms perceive in this context. It uses a new database on strategic alliances and traces the broader developments and nature of the international alliances of these Finnish firms. This is complemented with in-depth interviews of R&D managers. The results point to a rapid increase especially in the number of explorative alliances of ICT firms, and suggest that Finland participates in ”alliance capitalism” mainly as an explorer rather than exploiter of technologies. The main motives for forming alliances relate to risk and cost sharing and to complementary assets. Managerial and IPR issues provide the greatest challenges. The paper concludes with a discussion on implications for innovation policy.
Keywords: 330; strategic alliances; internationalisation; Finnish firms; Unternehmen; Finnisch; Strategische Allianz; Globalisierung